Chitinase activity potential and identification of chitinolytic bacteria isolated of swimmer crab’s cell - Sulistijowati, Rieny; Sudin, .; Harmain, Rita Marsuci (International Journal of Agricultural and Biological Engineering, 2021)
This study aimed at investigating the chitinase enzyme activity produced by chitinolytic bacteria from the skin of blue swimmer crab (Portunus pelagicus) and identification of the genus isolate. This study consists of two stages: firstly, the qualitative and quantitative activity of the chitinase enzyme; and secondly, biochemical identification of the bacteria. The quantitative chitinase enzyme activity is measured using the UV-Vis spectrophotometer UV-Vis at the wavelength at 660 nm. The chitinase enzyme is obtained from the isolation of chitinolytic bacteria cultured within a media to grow solid chitin, which contains colloidal chitin substrate as chitinase inductor at the temperature of 30°C. The highest chitinolytic activity is obtained from the 24 h supernatant culture, with a value of enzyme activity at 0.149 U/mL. Macroscopic and microscopic identification showed that the chitinolytic bacteria isolate R1, whereas the biochemical cell shows the characteristics of the genus Pseudomonas.Keywords: biodegradable, chitinase, spectrophotometer, Portunus pelagicus, PseudomonasDOI: 10.25165/j.ijabe.20211403.5273Citation: Sulistijowati R, Sudin, Harmain R M. Chitinase activity potential and identification of chitinolytic bacteria isolated of swimmer crab’s cell. Int J Agric & Biol Eng, 2021; 14(3): 228–231.